Peran Manajemen Risiko dalam Pengambilan Keputusan Brand Owner Entertaiment di Live House Indonesia - M Agung Akhdani (Premium Insurance Business Journal, 2024)
This research will discuss the role of risk management in decision making by entertainment brand owner in Live House Indonesia. The approach used this study is qualitative approach. The analysis in this research uses the stages of the ISO 31000 Risk Management process. This analysis begins with risk identification, risk analysis, risk evaluation, risk assessment, and risk control. The data sources for this research were obtained through in-depth interview with three informants. The result of this research is that by integrating or aligning risk management into every operational activity of entertainment live house in Indonesia entertainment brand owners are able to identify potential risks more quickly, evaluate risk faster, and make decisions more promptly. Furthermore, risk management plays a crucial role in decision-making for entertainment brand owner. By integrating risk management into every operational activity, entertainment brand owner can make wiser decisions.